Identifikasi Pencemaran Lingkungan Proses Produksi Pabrik Tahu Dengan Life Cycle Assessment - Fuadi, Muhammad Imam; Mirwan, Mohamad (Universitas Bojonegoro, 2023)
This study evaluates the environmental impact of the tofu production process using Life Cycle Analysis (LCA) with Simapro software. The goal is to identify environmental consequences, analyze their causes, and propose management strategies to mitigate impacts. LCA helps determine which stages of a product's life cycle contribute most significantly to environmental degradation, and to assess these impacts throughout the process. The Eco-Indicator 99(H) method identifies three main environmental effects: inorganic respiration, climate change, and carcinogenic emissions. Key contributing factors include the use of coagulants, firewood, and electricity. Recommendations for reducing these impacts include improving device efficiency, replacing acetic acid with nigarin as a coagulant, and utilizing residual soy milk from the settling process. These changes aim to make the tofu production process more sustainable while minimizing its environmental footprint.